Application Analysis of Buying and Selling Game to Grow the Language Development and Attitude of Entrepreneurs on Child Age 5-6 Years in Paud RA Al-Mahir - Rasti Purnamasari; Aman Simare-mare; Sri Minda Murni (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
This study aims: (1) to analyze the design of buying and selling games in Paud (early childhood education programs) on language development. (2) Knowing the selling game design process to foster entrepreneurial attitudes in Paud. (3) Realizing the reason for buying and selling games can foster the development of language and entrepreneurial attitudes. This type of research is a descriptive qualitative research that collects data directly at the source. Data analysis according to Miles and Huberman, namely: (1) data reduction, (2) data presentation, (3) inference and vertification. The results obtained from this study prove that the game of buying and selling can foster language development and entrepreneurial attitudes carried out on 3 children, namely 2 boys and one child is a girl. This research was conducted at Paud RA Al-Mahir Deliserdang.